Prevenção ao suicídio policial: um estudo do desenvolvimento de competências em equipe interdisciplinar do Departamento de Amparo Médico e Psicossocial (DAMPS), da Polícia Civil do Estado do Ceará. - Silva, Ana Cristina Lima e (2024)
As Brazilian and foreign studies show (Minayo, 2005; Miranda et al., 2016; Sousa, 2016; Hofmann; Glaesmer; Przyrembel; Wagner, 2021; Pinto et. al, 2021; Hawgood; Woodward; Quinnett; Leo, 2022; Pereira; Silva; Felgueiras; Queirós, 2023), police officers are among the professions with the highest risk of death by suicide. Therefore, public security institutions have been striving to welcome their professionals in a humanitarian and therapeutic way through a multidisciplinary team for this vital fight. For this performance, the literature presents skills to be developed by the service professionals of the team who work under different disciplines. The general objective of this work is to investigate how the professional skills of the medical and psychosocial support team (DAMPS) of the Ceará judicial police are being developed, considering the needs for providing mental health services to prevent police suicide. The research has three specific objectives, namely: to identify internal protocols carried out by DAMPS for the prevention and analysis of mental or psychological disorders of civil police officers, aiming at their reallocation for greater effectiveness of the essential public service, without a continuity solution; Verify the perception of the DAMPS team regarding the development and exercise of Communicative, Careful, Sociopolitical and Personal competencies, in addition to Cognitive, Behavioral, Attitudinal and Self-efficacy in preventing suicide among civil police officers and; Highlight the adequacy of these skills to deal with suicide prevention and possible situations that may affect the mental health of civil police officers. The present study is characterized as research with a qualitative approach, of an exploratory and descriptive nature, which seeks to investigate the development of skills, care protocols and institutional reception with the aim of preventing police suicide, especially after the Sars pandemic. -Covid. A semi-structured interview was used as a data collection instrument applied to DAMPS professionals who receive police officers. The time frame for studies of national competencies occurs after the Brazilian psychiatric reform. International competencies, in 2022, refer to the deaths that occurred and the lockdown situations that significantly altered people's mental health. This is especially true for those who had to work even in the face of this pandemic, for providing a necessary and uninterrupted public safety service. In general, the pandemic has shed light on the issue of mental health and the dire consequences of suicide. It was found that the skills studied are developed by the multidisciplinary team with an emphasis on welcoming that permeates all aspects of care. It was evident that although the gatekeeper course is not well known, the performance and training of professionals brings the characteristics of the guardian of life. In view of the single case study, each of the competencies carried out in the department was analyzed on a scale of Very Critical, Critical, Little Critical or Not Critical. From an experience point of view, all skills are widely developed by DAMPS, which deserves legitimacy, publicity of its services and expansion of its team to meet the demands of police officers.